Flora of the Serra do Cachimbo (Eastern Amazon, Brazil): Bambusoideae (Poaceae), including the description of two new species - Lopes-Neto, Raimundo Balieiro; Viana, Pedro Lage (Phytotaxa, 2022)
This paper is a floristic and taxonomic treatment of the native bamboos from the Serra do Cachimbo, Eastern Amazon, Brazil. Two collection expeditions were carried out in 2019 and 2021, in addition to the analysis of materials from herbaria. Ten genera and 17 species were found. Descriptions, identification keys, distribution and habitat data, taxonomic comments, and photographs are provided, along with illustrations and conservation status assessment for two new species. The most speciose genus was Olyra (four species), followed by Raddiella (three), Arthrostylidium (two), and Pariana (two); Actinocladum, Eremocaulon, Guadua, Merostachys, Parodiolyra, and Taquara were represented by one species each. Four species are here recorded for the first time for the states of Pará (Arthrostylidium simpliciusculum and Eremocaulon capitatum) and Mato Grosso (Pariana radiciflora and P. zingiberina). We also designate a lectotype for the basionym of E. capitatum and describe two new taxa to science: Arthrostylidium cachimboense and Merostachys cachimboensis.